Industry Share in Total Output Vs. GDP Per Capita - Piotr WALAG; Dominika GORKA (Communications of International Proceedings, 2025)
On the basis of recent studies on changes in the structure of economies, it is becoming problematic to assess the process of deindustrialization. It is not clear whether deindustrialization, when industry is the main engine of economic growth, is detrimental or beneficial to development and economic growth. The aim of this study is to analyses changes in the share of industry in total output, as well as the structure of the economy's output itself in its development, and the impact of this process on the level of GDP per capita. A statistical analysis of changes in the structure of global production in the Polish economy between 1995 and 2023 was used, which showed that although the share of industry in total global production at current prices remains almost constant, its real share in total global production volume at constant prices is increasing very strongly, while also having the largest and fastest-growing real share in total global production volume of all sectors of the economy. Hence, the level of global production volume for the entire economy was mainly shaped by the real share of industry in total global production volume. A multifactor econometric analysis also showed that during the period under review, the level of GDP per capita was most strongly determined by the real share of industry in the volume of total output.
Keywords: Deindustrialization; Output; Industry.